The utility of sentinel Lymph node biopsy in the lateral neck in papillary thyroid carcinoma - Yan, Xing-qiang; Ma, Zhao-sheng; Zhang, Zhen-zhen; Xu, Dong; Cai, Yang-jun; Wu, Zeng-gui; Zheng, Zhong-qiu; Xie, Bo-jian; Cao, Fei-lin (Frontiers in Endocrinology, 2022)
Background. Regional lymph node metastases (LNM) are very common in papillary thyroid carcinoma (PTC) and associate with locoregional recurrence. The appropriate management of cervical lymph nodes is very important. Therefore, this study was to evaluate the application of sentinel lymph node biopsy (SLNB) in the lateral neck in PTC patients. Methods: This prospective study was conducted from 1 November 2015 to 31 December 2017 and recruited 78 PTC patients treated with SLNB in the lateral neck and prophylactic lateral neck dissection (compartments II-IV) followed by thyroidectomy or lobectomy and central neck dissection. Results: There were 78 PTC patients enrolled and sentinel lymph nodes (SLN) were detected among 77 patients. 30 patients were diagnosed with SLN metastases (SLNM). The remaining 47 patients were pathologically negative of SLN, whereas 4 patients were found with metastases in the non-SLN samples. The detection rate, sensitivity, specificity and accuracy rate of SLNB in the lateral neck were 98.7%, 87.1%, 98.7% and 93.6%, respectively. However, the values varied greatly in each specific compartment of the lateral neck and all of them were no more than 80%. These 34 PTC patients diagnosed with lateral compartment LNM (LLNM) were more likely to be younger (41.38 vs. 48.95 years old, p = 0.002), and exhibit extrathyroidal extension (56.8% vs. 31.7%, p = 0.026) and central compartment LNM (66.7% vs. 12.1%, p < 0.001). Tumors located in the upper third of the thyroid lobe also had a significantly higher probability of LLNM compared with those in middle or inferior location (66.7% vs. 35.3% vs. 34.8%, p = 0.044). At last, age (OR=0.912, p = 0.026), tumor location (upper vs inferior, OR=17.478, p = 0.011) and central compartment LNM (OR=25.364, p < 0.001) were independently predictive of LLNM. Conclusions: SLNB can help surgeons to identify some PTC patients who may benefit from therapeutic lateral neck dissection and protect some patients from prophylactic lateral neck dissection, but it cannot accurately indicate specific lateral compartment-oriented neck dissection. Meanwhile, LLNM is more likely to occur in PTC patients with younger age or upper pole tumors or central compartment LNM.